Analisis Daya Dukung Wilayah untuk Pengembangan Sapi Bali di Kecamatan Baito Kabupaten Konawe Selatan - M Abadi; L O Nafiu; R Libriani; R Rahman; G Gerhana (Politeknik Negeri Lampung, 2023)
Analysis of the carrying capacity of the region is needed as an appropriate development direction. This study aims to analyze the carrying capacity of the area for the development of Bali cattle in Baito District, South Konawe Regency. The data used in the study are primary. Primary is obtained directly from interviews with Balinese cattle farmers in Baito District. The method used is the census method of all breeders. The data analysis used in this study was livestock density analysis. Based on the results of the study, it was concluded that economic density can still be developed, the density of agricultural businesses is possible to accommodate Balinese cattle to be developed, and the density of the area is still very likely. Baito sub-district is based on a combination of livestock density, which includes distribution and development areas in a combination of farmer-region and development areas in 2 combinations, namely economy-farming and economy-region.